Turner's syndrome with coeliac disease, thin bones and abnormal liver function tests. Issue 576 (October 1973) - Thatcher, N.; Stephens, A. D.; Besser, G. M.
Abstract : A patient is described with 45 XO Turner's syndrome and thin bones. It transpired that the patient had osteomalacia due to gluten sensitive enteropathy rather than the osteroporosis usually expected with Turner's syndrome. In addition, she had unexplained liver dysfunction. Causes for thin bones other than the osteoporosis associated with ovarian agenesis should be considered in patients with Turner's syndrome.